Field-based tests for determining critical speed among runners and its practical application: A systematic review - Lipková, L.; Struhár, I.; Krajnák, J.; Puda, D.; Kumstát, M. (Frontiers in Sports and Active Living, 2025)
Introduction: This review focuses exclusively on field-based critical speed (CS) tests for runners, aiming to evaluate key testing conditions to optimize field-based assessments and their practical applications.